Olhos atentos braços fortes pra enegrecer, juventude negra organizada para tomar o poder: Serviço Social, raça/etnia o debate no interior do movimento estudantil - Silva, Helen Cristina Ferreira da (Universidade Federal do Tocantins, 2021)
This course conclusion paper entitled “STRONG EYES STRONG ARMS TO BLACK, BLACK YOUTH ORGANIZED TO TAKE POWER: SOCIAL SERVICE, RACE/ETHNY THE DEBATE INSIDE THE STUDENT MOVEMENT”, aims to identify the perceptions of students in the region ENESSO's IV on race, gender and ethnicity in the period from 2019 to 2020 In this path, we seek to identify the perceptions of students from the region of ENESSO IV on race, gender and ethnicity. The bibliographic research method was used to collect information about the history of the Brazilian Student Movement, as well as empirical research, to understand the political historical context of federal universities in Brazil. Jointly bringing debates on: gender, race and ethnicity within Social Work, the historicity of the Student Movement of Social Work and its relationship with the theme race and ethnicity. The qualitative methodology was necessary, given that, through an applied questionnaire, it evidenced the importance of racial debate within higher education institutions. Finally, it was found that it is not enough to just expand access and promote affirmative policies for black students, a public, secular and quality education and greater investment in assistance actions, such as PNAES, that serve the entire academic community, should be offered. and together an expansion in the debate about race, ethnicity and gender in universities.